Back to the roots, desiccation and radiation resistances are ancestral characters in bdelloid rotifers - Hespeels, Boris; Fontaneto, Diego; Cornet, Valérie; Penninckx, Sébastien; Berthe, Jérémy; Bruneau, Lucie; Larrick, James W; Rapport, Eloïse; Bailly, Jérémie; Debortoli, Nicolas; Iakovenko, Nataliia; Janko, Karel; et al. (BMC biology, 2023)
BACKGROUND: Bdelloid rotifers are micro-invertebrates distributed worldwide, from temperate latitudes to the most extreme areas of the planet like Antarctica or the Atacama Desert. They have colonized any habitat where liquid water is temporarily available, including terrestrial environments such as soils, mosses, and lichens, tolerating desiccation and other types of stress such as high doses of ionizing radiation (IR). It was hypothesized that bdelloid desiccation and radiation resistance may be attributed to their potential ability to repair DNA double-strand breaks (DSBs). Here, these properties are investigated and compared among nine bdelloid species collected from both mild and harsh habitats, addressing the correlation between the ability of bdelloid rotifers to survive desiccation and their capacity to repair massive DNA breakage in a phylogenetically explicit context. Our research includes both specimens isolated from habitats that experience frequent desiccation (at least 1 time per generation), and individuals sampled from habitats that rarely or never experienced desiccation. RESULTS: Our analysis reveals that DNA repair prevails in somatic cells of both desiccation-tolerant and desiccation-sensitive bdelloid species after exposure to X-ray radiation. Species belonging to both categories are able to withstand high doses of ionizing radiation, up to 1000 Gy, without experiencing any negative effects on their survival. However, the fertility of two desiccation-sensitive species, Rotaria macrura and Rotaria rotatoria, was more severely impacted by low doses of radiation than that of desiccation-resistant species. Surprisingly, the radioresistance of desiccation-resistant species is not related to features of their original habitat. Indeed, bdelloids isolated from Atacama Desert or Antarctica were not characterized by a higher radioresistance than species found in more temperate environments. CONCLUSIONS: Tolerance to desiccation and radiation are supported as ancestral features of bdelloid rotifers, with a group of species of the genus Rotaria having lost this trait after colonizing permanent water habitats. Together, our results provide a comprehensive overview of the evolution of desiccation and radiation resistance among bdelloid rotifers.
Keywords: Rotifera; Atacama Desert; Humans; DNA Breaks, Double-Stranded; DNA repair; dvouřetězcové zlomy DNA; oprava DNA; vířníci; lidé; zvířata; Bdelloid rotifers; DNA Repair; Extreme tolerance; vysoušení; Ancestral character reconstructions; Antarctica; voda; Water; Animals; Desiccation